COSFoTS: component oriented software framework for telecommunication software - HUANG Xing-ping; LONG Xiang-ming; XU Peng; YANG Fang-chun (Tongxin xuebao)
Based on the research of software framework and analysis on telecommunication software,component ori-ented software framework for telecommunication software（COSFoTS） was put forwared.The architecture and the key issues of COSFoTS,such as software bus based kernel design,the orthogonal decomposition of functional components and ALDL（application logic description language）based application logic generation were specified.Moreover,the soft-ware development process using COSFoTS was also introduced.COSFoTS had been put into practice in the development of telecommunication software "soft switch controller supporting multimedia and mobile service",and was proved to be effective on simplifying the development of telecommunication software and improving the quality of telecommunication software products.